The parasite complex of Saissetia nigra in Malaysia - Tock, Hing Chua (Kluwer Academic Publishers, 1978)
The percentage parasitism of Saissetia nigra (NIETNER) by chalcidoid parasites and the relative abundance of individual parasites were studied in the field usingHibiscus rosa-sinensis L. as the host plant. In order of abundance (on the basis of percentage recorded) the primary parasites wereAnysis saissetiae ASH.,Aneristus ceroplastae HOW., and Microterys newcombi (GIR)., while the hyperparasites wereMarietta exitiosa COMP.,Cheiloneurus saissetiae NOYES & CHUA andEupelmus catoxanthae FERR. The efficiency ofA. saissetiae (the larvae of which feed on the scale eggs) to control the scale population is doubtful because it is often parasitised by all 3 hyperparasites mentioned and each larva during development causes only 58% egg mortality of the parasitised host, leaving many scale eggs unconsumed.A. ceroplastae appears to be more useful parasite because it attacks the 2nd instar scales which cause significant damage to the host plant and it is free from attack by hyperparasites.